The Veneration of spolia: the Madonna della Colonna in St. Peter’s in Rome (Fenestella. Inside Medieval Art, 2020)
In the context of the history of planning, designing and constructing new St. Peter’s the concepts of renewal and continuity can be insightful. Renewal was the essence of the plans of Pope Julius II (1503-1513) of around 1505, since the wording in documents points to renewal instead of replacing the old church completely: words like reparare et exornare, rehedificare and instaurare were used. When in the early 17th century pope Paul V decided to tear down the remainder of the old basilica, the chapter feared that many of the monuments, altars and tombs in the old basilica would disappear, which would diminish the visibility of the continuity of the basilica and its chapter.One of those objects was the so-called Madonna della Colonna, a fresco of the Virgin and Child painted on the third column on the left in the old basilica. This miracle-working image became increasingly popular in the last quarter of the 16th century was officially recognized when in 1578 an altar was installed to direct the cult. This underlines the situation where the remaining eastern part of Old St. Peter’s still functioned as the important basilica, while to the west the new building was gradually being constructed. Both the history of planning and designing the renewal of St. Peter’s and the continuous functioning of the remaining eastern part of the early Christian basilica shows that both renewal and continuity were crucial here. One of the elements judged necessary to ensure continuity was the Madonna della Colonna, which was thus transferred to a new altar in new St. Peter’s.
Keywords: Antica San Pietro in Vaticano; Spolia; Arte medievale; Architettura medievale